Sexual problems of women aged 60+ with diagnosed obesity - Agnieszka Pawełko; Maria Ciechacka; Ewelina Bąk (Journal of Education, Health and Sport)
Introduction Sexuality is a complex issue, but every person has the right to express it. Seniors are individuals with significant life experience. They are often curious people with much to say to younger generations. Let us allow them to function fully in society, respecting all spheres of life, allowing them to express their sexuality and diversity.